A Theory of Minsky Super-Cycles and Financial Crises - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2009)
This paper argues that Hyman Minsky's financial instability hypothesis weaves together a medium term Keynesian approach to the business cycles in the spirit of Samuelson (1936) and Hicks (1950) with long cycle thinking of economists such as Schumpeter (1939) and Kondratieff. Post Keynesians have devoted considerable attention to the medium term dimension of Minsky's thinking. The current paper concentrates on the long swing dimension and introduces the idea of "Minsky super-cycles." It is the supercycle that ultimately permits financial crisis. Whereas financially driven business cycles occur every decade, financial crises occur over longer durations reflecting the longer phase of the super-cycle.
urn:nbn:de:101:1-2009071381
Keywords: 330; Minsky; business cycles; financial instability hypothesis